Relationship between Inferior Thyroid Artery and Recurrent Laryngeal Nerve - A Study of 200 Cases - Azad, Muhammad Ali; Asaduzzaman, AKM; Hossain, Mohammad Delwar; Mohsin, Faysal Bin; Safi, Abdullahis (Bangladesh Journal of Otorhinolaryngology, 2020)
Introduction: Thyroid surgery is a common modality of treatment for both benign and malignant thyroid disorders.Relationship between inferior thyroid artery (ITA) and recurrent laryngeal nerve (RLN) is crucial in preservation of recurrent laryngeal nerve. Thorough anatomical knowledge and meticulous surgery will ensure the integrity of recurrent laryngeal nerve. Objective: The purpose of this study is to observe the anatomical position of recurrent laryngeal nerve in relation to inferior thyroid artery which will eventually lead to identification of recurrent laryngeal nerve peroperatively. Methods: A cross sectional retrospective study was conducted during the time period of 1st January 2013 to 31st December 2015 in Combined Military Hospital, Dhaka among 200 patients who had undergone thyroidectomy. Results: In this series on the right side 71.8% cases RLN was dorsal to ITA, 21.7% cases it was ventral and in 6.5% cases RLN runs in between the branches of ITA. In case of left side 74.5% cases RLN was dorsal to ITA, 22.5% cases it was ventral and in 3% cases RLN runs in between the branches of ITA. Conclusion: Usually RLN runs dorsal to ITA. In left side it is deeper and in case of right side it is more superficial. RLN may pass through the branches of ITA, but it is not very common. Bangladesh J Otorhinolaryngol; October 2016; 22(2): 60-65